New data on winter crane flies (Diptera: Trichoceridae) of Korea with description of a new species - Petrašiūnas, Andrius; Podenas, Sigitas (Zootaxa, 2017)
Species of Trichoceridae Rondani known to occur on the Korean Peninsula are reviewed; eight of these are recorded for Korea for the first time. Trichocera (Saltrichocera) sapporensis Alexander, 1935 and T. (S.) maculipennis pictipennis Alexander, 1930 are proposed as synonyms of T. (S). maculipennis punctipennis Brunetti, 1912 which is transferred to a subspecific rank. A new species—Trichocera (Saltrichocera) latipons sp. nov. is described.